The Role of Women in Islamic Political Movements: A Feminist Perspective - Arifin, Muhammad (Journal International Dakwah and Communication, 2024)
Women have historically played a crucial yet often overlooked role in Islamic political movements, contributing to ideological development, grassroots mobilization, and policy advocacy. While dominant narratives frequently portray Islamic political movements as male-dominated, feminist scholarship highlights the agency of women in shaping political discourse within Islamic frameworks. The intersection of gender, religion, and politics remains a complex area of study, requiring a nuanced understanding of how women navigate and influence Islamic political spaces. This study aims to examine the roles, challenges, and contributions of women in Islamic political movements through a feminist analytical lens. A qualitative research approach was employed, incorporating in-depth interviews with female activists, content analysis of political discourse, and historical case studies from various Islamic political movements. Findings reveal that women engage in diverse roles, ranging from grassroots activism to leadership positions, despite facing structural and ideological barriers. Religious reinterpretation, digital activism, and coalition-building emerge as key strategies employed by women to assert their political agency. The study concludes that while women’s participation in Islamic political movements is expanding, persistent gender hierarchies necessitate continuous efforts toward inclusivity and representation. These findings contribute to feminist and political discourse by providing empirical insights into the evolving role of women in Islamic political spheres